Percutaneous endocardial septal radiofrequency ablation in patients with hypertrophic obstructive cardiomyopathy - Tian, Aiju; Cheng, Yunjiu; Jia, Yuhe; Zhang, Tianjing; Li, Jiaju; Chen, Xuhua; Liu, Jun; Guo, Xiaogang; Sun, Qi; Tang, Min; Chen, Keping; Yao, Yan (BMC cardiovascular disorders, 2025)
Percutaneous endocardial septal radiofrequency ablation (PESA) shows promise as a treatment for hypertrophic obstructive cardiomyopathy (HOCM). We aimed to explore the efficacy and safety of PESA require further study during a long-term follow-up. We enrolled 25 patients HOCM who underwent PESA. The combination of a three-dimensional electrophysiological mapping system and intracardiac echocardiography (ICE) was employed to guide PESA. The patients were followed for 37 months (25-47.5 months), with transthoracic echocardiography performed 22 months (8-29 months) after the procedure. The mean age of patients was 55.3 ± 13.5 years (range: 23 to 79), and 11 (44%) of them were female. PESA led to a significant reduction in the left ventricular outflow tract gradient (LVOTG) from 79.0 ± 37.6 mmHg to 55.6 ± 34.8 mmHg (p = 0.002), as well as syncope episodes (60% vs. 19%, p = 0.0039) in patients with HOCM. The New York Heart Association (NYHA) functional class of the patients was improved from 2.14 ± 0.57 to 1.76 ± 0.54 (p = 0.002). In 10 patients undergoing cardiovascular magnetic resonance imaging (CMRI) both before PESA and at a follow-up of 3-6 months, the maximum left ventricular outflow tract velocity was ameliorated from 232.6 ± 56.8 m/s to 159.4 ± 46.9 m/s (p = 0.024). Besides, the minimum systolic diameter of left ventricular outflow tract was increased from 3.84 ± 2.6 mm to 6.3 ± 2.3 mm (p = 0.0006). There were no instances of cardiac tamponade, lethal arrhythmia, or death. Four patients underwent surgical septal myectomy during the follow-up. PESA could attenuate LVOT obstruction and improve heart function in patients with HOCM during a long-term follow-up. PESA may be an effective and safe treatment for HOCM.